People management for managing employees' retention in the organizations - Mohd Rasdi, Roziah; Yong, See Chen (Human Resource Management Academic Research Society, 2018)
Changes in the career and organizational landscape have brought tremendous effect to employees’ career, and result to blurring of organizational boundaries. Such unpredictable events influence employees’ retention in the organizations. The paper aims to examine the factors contributing to employees’ retention in the organizations. This conceptual paper theorizing employees’ retention using job embeddedness theory and Herzberg’s two factor theory. Voluminous number of studies concluded that the determinants of employees’ retention can be categorized as the job factors and motivational factors. These two factors are highly associated with the HR practices in the organizations which include attracting, motivating, rewarding and retaining employees through a bundle of job policies, practices and systems. The paper emphasizes on the importance of HRD practices in managing employees’ retention, and highlights the dominance of HRD interventions in retaining employees in the organizations.